If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -7 = 7y + 7 Reorder the terms: -7 + 9y = 7y + 7 Reorder the terms: -7 + 9y = 7 + 7y Solving -7 + 9y = 7 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -7 + 9y + -7y = 7 + 7y + -7y Combine like terms: 9y + -7y = 2y -7 + 2y = 7 + 7y + -7y Combine like terms: 7y + -7y = 0 -7 + 2y = 7 + 0 -7 + 2y = 7 Add '7' to each side of the equation. -7 + 7 + 2y = 7 + 7 Combine like terms: -7 + 7 = 0 0 + 2y = 7 + 7 2y = 7 + 7 Combine like terms: 7 + 7 = 14 2y = 14 Divide each side by '2'. y = 7 Simplifying y = 7
| 13x+19y=23 | | -6x+4=-4x+2 | | -6b+62=8b+6 | | 3x-3y+7=0 | | 17x-28x-12=21 | | Y+13.4=8.63 | | 2r+10=14 | | 3/5a=18 | | 18b-6= | | -1x+9=7x-5 | | x^6-4x^5+13x^4=0 | | z^4+4iz+10i=0 | | -16y+18=-30 | | (1/5)^(x-9)=5^(7x-5) | | -3+8x=-59 | | 75=25t+4.9t^2 | | 0.6(x-4)=12.0 | | 38a+21-20a=39 | | -1x-9=7x+5 | | 75=25*t+0.5*9.8*t^2 | | 9(x+4)+x=3(x+5)-8 | | -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 |